Танец тюльпанов: [роман] / Ибон Мартин ; [перевод с испанского К. Никишёвой] - Мартин Ибон (Inspiria, 2021)
Экземпляры: с/ф № 8 (20241128) / Инвентарный номер: 52803 / Цена: / Авт.знак: М 29 / ГРНТИ: 17.82.31 / ББК: 84(4Исп)6-44